2013
DOI: 10.1007/s00264-013-2137-5
|View full text |Cite
|
Sign up to set email alerts
|

Metal-on-metal hip prostheses: Correlation between debris in the synovial fluid and levels of cobalt and chromium ions in the bloodstream

Abstract: Purpose Hip prostheses with metal-on-metal (MoM) coupling can release cobalt-chromium particles and ions. The aim of this work is to verify the correlation between particles in the synovial fluid and circulating ions. Methods Forty patients were enrolled; particles from synovial fluid were analysed by SEM-EDX (Scanning Electron Microscopy-Energy Dispersion X-rays analysis) and levels of circulating Co and Cr were assayed by ICP-MS (inductively-coupled plasma mass spectrometry). Results In 16 cases we did not f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 31 publications
1
22
0
Order By: Relevance
“…It is clear that conventional follow-up methods (i.e., plain radiographs and clinical followup) are not sufficient to identify ARMeD in patients with MoM hips [4]. Hence metal ion assessment both from blood and synovial fluid, in addition to cross-sectional imaging, have been used to detect articulation related complications [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…It is clear that conventional follow-up methods (i.e., plain radiographs and clinical followup) are not sufficient to identify ARMeD in patients with MoM hips [4]. Hence metal ion assessment both from blood and synovial fluid, in addition to cross-sectional imaging, have been used to detect articulation related complications [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Metal ion levels have been extensively used as a surrogate marker for patients with MoM bearings related wear 45. The population background level of Co in blood has been shown to be 0.5 μg/L, and the mean Co blood levels in patients with well functioning MoM hip implants ranges between 0.2 and 4 μg/L 46.…”
Section: Introductionmentioning
confidence: 99%
“…This debris dissolves in the synovial fluid and disperses through the body via the bloodstream. Prior studies have shown good correlation of blood and synovial fluid metal levels [12,13]. Typically, the blood levels of cobalt and chromium, in a well-functioning SRA, are in the order of 2-3 parts per billion [14][15][16].…”
Section: Metal Ion Dispersalmentioning
confidence: 99%